Role of Etomidate in Critical Care for Rapid Sequence Intubation - Kumar, Vishnu; Raj, Ajay K; Mahroof, Rasha; Fabin, M; M, Ansil (Indian Journal of Pharmacy Practice)
Rapid sequence intubation is a process involving the administration of a sedative induction agent and a paralytic agent to facilitate endotracheal intubation. Administration of an induction agent followed by a rapidly acting neuromuscular blocking agent to produce unconsciousness and motor paralysis provide optimal intubation condition and protect the patient’s airway. Etomidate is gamma amino butyric acid agonist administered to facilitate a state of unconsciousness; it has a rapid onset of action and duration of action for 4-10 min, minimal cardiovascular effects, respiratory depression of histamine release and provides protection from myocardial and cerebral ischemia. This review discuss the importance of Etomidate as the first line induction agent in emergency department. A detail literature review of rapid sequence intubation in emergency department was carried out from PubMed using the keywords Etomidate, Ketamine, Propofol, Rapid sequence intubation. Etomidate is the first line drug in thermodynamically stable patients and in traumatic brain injury. However, it should not be used as an infusion or as repetitive bolus doses for maintenance dosage adjustment in elderly patients. Etomidate when used provides sedation within 1 min and eliminates critical monitoring requiring only basic monitoring parameters like blood pressure, pulse and ECG readings. Incidence of hypotension is low and when occurs can be managed with IV fluids, the sedation lasts for about 30 mins. However patient specific factors must also be considered during the selection of intubating agent.
Keywords: Rapid; Sequence intubation; Etomidate; Ketamine; Propofol; ECG changes.